THE SPIRITUAL MEANING AND PURPOSE OF LOVE IN THE WORKS OF CHINGIZ AITMATOV (American Journal of Interdisciplinary Research and Development, 2025)
This article examines the theme of love in the works of Chingiz Aitmatov as a spiritual and moral phenomenon. The author analyzes the following forms of love in the writer's works: • a means of moral development; • a means of self-knowledge and spiritual poverty; • a way to overcome abstract loneliness; • the connection between tradition and personal freedom.